Polymorphisms of Vitamin D Receptor and the Effect on Metabolic and Endocrine Abnormalities in Polycystic Ovary Syndrome: A Review - Vulcan, Talida; Filip, Gabriela Adriana; Lenghel, Lavinia Manuela; Suciu, Tudor; Ilut, Paula; Procopciuc, Lucia Maria (Hormone and Metabolic Research, 2021)
Polycystic ovary syndrome (PCOS) is one of the most prevalent endocrine disorder in women of reproductive age. Vitamin D and its receptor are thought to play an important role in PCOS susceptibility, although the impact of vitamin D receptor (VDR) polymorphisms on the hormonal and metabolic profile is still controversial. A literature search in PubMed and Embase was performed up to September 2020 for case-control studies in women suffering from PCOS, with outcome related to VDR polymorphisms effect on metabolic/endocrine disturbances. We have found 16 eligible studies including 2566 women with PCOS and 2430 controls. ApaI polymorphism seemed to be associated with hyperandrogenism in both Asian and Caucasian population. FokI variant was correlated with metabolic/endocrine parameters especially in Asian population, while a relation between Cdx2 genotypes and insulin sensitivity was observed in both ethnicities. VDR polymorphisms have an important role in PCOS development and related hormonal and metabolic abnormalities. Few case-control studies analysed the interaction between VDR variants and metabolic/endocrine parameters with the majority of the articles focused on the Asian region. Further research on various ethnic populations with larger sample size are still needed for a definitive conclusion, in order to allow early diagnosis and prevention of PCOS comorbidities.
Keywords: vitamin D receptor polymorphism; PCOS; hyperandrogenism; insulin resistance